Global and Local Conformation of Human IgG Antibody Variants Rationalizes Loss of Thermodynamic Stability. (20th October 2015) - Edgeworth, Matthew J.; Phillips, Jonathan J.; Lowe, David C.; Kippen, Alistair D.; Higazi, Daniel R.; Scrivens, James H.
Abstract: Immunoglobulin G (IgG) monoclonal antibodies (mAbs) are a major class of medicines, with high specificity and affinity towards targets spanning many disease areas. The antibody Fc (fragment crystallizable) region is a vital component of existing antibody therapeutics, as well as many next generation biologic medicines. Thermodynamic stability is a critical property for the development of stable and effective therapeutic proteins. Herein, a combination of ion‐mobility mass spectrometry (IM‐MS) and hydrogen/deuterium exchange mass spectrometry (HDX‐MS) approaches have been used to inform on the global and local conformation and dynamics of engineered IgG Fc variants with reduced thermodynamic stability. The changes in conformation and dynamics have been correlated with their thermodynamic stability to better understand the destabilising effect of functional IgG Fc mutations and to inform engineering of future therapeutic proteins.